KATA PINJAMAN BAHASA INGGRIS DALAM ISTILAH MEDIS - Poluakan, Handy Stevanus; Pamantung, Rina P.; Rambing, Rosalina R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTThis research entitled ?Kata Pinjaman Bahasa Inggris dalam Istilah Medis Indonesia?. The objectives of research are to find out the kinds and the changes of the meanings of English loanwords in Indonesian language. In analysing the data, the writer uses Haugen?s theory to find out the types and Baugh?s theory to get the changes of the meanings. To support the analysis, the writer uses Oxford Dictionary and Kamus Besar Bahasa Indonesia. The result of this research show that based on the theory of Haugen there are three kinds of loanword. Those are loanword without phonemic substitution, loanword with partial phonemic substitution, loanword with complete phonemic substitution and there are two kinds of the changes of meaning such as extension, narrowing, regeneration, and degeneration. Keywords: Loanwords, Changes of meaning, Medical terminology, Sociolinguistics